Sovereign credit rating system and determinants of short term sovereign risk: evidence from Turkey - Altay, Osman (My University, 2015)
Bu çalışmada, Türkiye’nin ülke kredi riski, ekonomik, mali, parasal ve olay risk faktörleriyle Türkiye’nin ülke kredi notları arasındaki ilişki analiz edilerek sorgulanmıştır. Türkiye’nin ülke riskiyle ilişkili kısa dönem değişkenler zaman serisi analizi modellemesi yapılarak belirlenmiştir. Kredi derecelendirme kuruluşlarının ülkelerin mevcut durumlarını yansıtmada başarısız olduklarına dair eleştiriler dikkate alındığında, kredi notları ve ülke riski üzerinde etkili olan kısa dönem değişkenlerin belirlenmesi büyük bir önem kazanmaktadır. Derecelendirme kuruluşlarının ülke kredi notları üzerinde potansiyel etkisi olduğu umulan değişkenler istatistik ve ekonometri analiz olan Eviews kullanılarak, zaman serisi analizinin en küçük kareler yöntemi metoduyla analiz edilmiştir. Çalışma iki bölümden oluşmaktadır. İlk bölümde ülke kredi derecelendirme sistemi; borçlanmanın içeriği, sistemin tarihi ve sisteme yöneltilen eleştirilerle ülke riski ve kredi derecelendirme sistemi alt başlıklarıyla açıklanmaktadır. İkinci bölümde ise bu tezin ampirik çalışması yorumlar ve önerilerle birlikte sunulmaktadır.

In this study, sovereign risk of Turkey has been examined analyzing the relations among economic, fiscal, money market, event risk factor variables and sovereign credit rates of Turkey. Short term variables which are in association with sovereign risk of Turkey have been determined through time series analysis modeling. Considering the critiques regarding credit rating agencies not being able to reflect current situations of sovereigns, determination of those short term variables effective on the credit rates and sovereign risk is gaining a great importance. Variables which are thought to have effect on the sovereign credit rates of the agencies are investigated through least square methodology of the times series analysis using Eviews software of statistical and econometric analysis. The study consists of two parts. In the first part of the study, sovereign credit rating system is explained within the context of the borrowing, country risk and credit rating with the history and critiques of the system. In the second part empirical study is conducted and results are presented with interpretations and suggestions. Key Words: Credit Rating Agencies, Sovereign Rating, Credit Rating System, Country Risk, Credit Default Swaps, CDS, Eurobond Spreads, Standard & Poors, Moody’s, Fitch
Keywords: Kredi derecelendirmesi; Kredi kontrolü; Muhasebe